141 Association between firearm laws and homicide among emerging adults. (5th May 2020) - Crifasi, Cassandra; McCourt, Alexander; Webster, Daniel
Abstract : Statement of Purpose: To assess the impact of firearm laws on homicides among emerging adults (age 18–20) as they are disproportionately victimized in firearm homicide. Methods/Approach: We conducted an interrupted timeseries using negative binomial regression with state and year fixed effects to assess the impact of firearm laws on homicide among those age 18–20 between 1989–2015. Homicide was stratified by firearm and nonfirearm to test for specificity of the laws' effects. Laws were coded as 0 pre-implementation and 1 for the first full year post-implementation. Models controlled for several state demographic characteristics. Age appropriate sub-populations were used to calculate Incident Rate Ratios (IRR). Results: Among emerging adults, handgun purchaser licensing laws (IRR=0.62, 0.50–0.77), large capacity magazine bans (IRR=0.80, 0.69–0.92), and prohibitions for violent misdemeanors (IRR=0.86, 0.76–0.96) were associated with reductions in firearm homicide. Background check alone (IRR=1.12, 1.02–1.24) and shall issue laws without discretion (IRR=1.18, 1.05–1.31) were associated with increases in firearm homicide. Compared to current may issue concealed carry, no issue of permits was also associated with increases in firearm homicide (IRR=1.15, 1.02, 1.29). No policies were associated with changes in nonfirearm homicide. Conclusions: Laws requiring background checks are conducted as part of a licensing system, banning ownership among those convicted of a violence misdemeanor beyond domestic violence, and limiting magazine size are associated with reductions in firearm homicide among emerging adults. Laws that make it easier to for civilians to carry guns in public are associated with increases in firearm homicide. Significance and Contributions of Injury and Violence Prevention Science: Emerging adults experience disproportionately high rates of firearm homicide. This is the first study to estimate the impact of firearm laws on homicide of emerging adults and offers specific policy solutions to reduce gun violence in this age group.